Legal and Operational Challenges in Contemporary Governance and Business: Structural Tensions, Regulatory Complexity and Strategic Adaptation - Jyothi M.R., (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2026)
The contemporary regulatory and institutional environment is characterized by an unprecedented convergence of legal complexity and operational vulnerability. Globalization, technological transformation, cross-border commerce, and evolving governance norms have reshaped the relationship between legal compliance and operational functionality. Organizations today must operate within multilayered legal frameworks while maintaining efficiency, innovation, and competitiveness. This research article examines the structural tensions between legal mandates and operational realities, focusing on regulatory fragmentation, jurisdictional conflicts, technological disruption, corporate governance obligations, and crisis management liabilities. Through doctrinal analysis, comparative institutional review, and policy evaluation, the article explores major regulatory developments including the General Data Protection Regulation, the Sarbanes-Oxley Act, and multilateral trade governance under the World Trade Organization. The study argues that legal-operational misalignment constitutes one of the defining governance challenges of the twenty-first century and proposes an integrated compliance and risk-based regulatory model to enhance institutional resilience.
Keywords: Legal Compliance; Operational Risk; Regulatory Governance; CrossBorder Regulation; Corporate Accountability; Digital Law